2019
DOI: 10.1155/2019/5319456
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Ameliorated the Development of Chronic Kidney Disease in Patients with Chronic Hepatitis C: A Retrospective Population-Based Cohort Study

Abstract: Chronic kidney disease (CKD) is a serious complication affecting patients with chronic hepatitis. The effectiveness of CHM for the prevention of CKD in hepatitis patients remains unclear. Therefore, we conducted a retrospective cohort study to investigate the effectiveness of CHM in preventing the development of CKD in hepatitis patients. From a subdataset of the Taiwan National Health Insurance Research Database (NHIRD), we included 19,409 patients newly diagnosed with hepatitis B and hepatitis C between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This result was similar to that of from another retrospective population-based cohort study among hepatitis patients. 19 Its components are believed to reduce the blood pressure and exert anti-oxidative, anti-fibrotic, and anti-thrombotic effects. Tetrahydropalmatine, one of the active components isolated from Yan-Hu-Suo, was found to possess antihypertensive activity by decreasing hypothalamic serotonin and noradrenaline release in the rodent model.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to that of from another retrospective population-based cohort study among hepatitis patients. 19 Its components are believed to reduce the blood pressure and exert anti-oxidative, anti-fibrotic, and anti-thrombotic effects. Tetrahydropalmatine, one of the active components isolated from Yan-Hu-Suo, was found to possess antihypertensive activity by decreasing hypothalamic serotonin and noradrenaline release in the rodent model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a randomized controlled trial showed Bupi yishen formula mitigated patients with non-diabetic stage 4 CKD ( Mao et al, 2020 ). Moreover, a retrospective population-based cohort study showed that Chinese herbal medicine, such as Salviae miltiorrhizae and Jia-Wei-Xiao-Yao-San, mitigated CKD in patients with chronic hepatitis C ( Chang et al, 2019 ). So far, although TCMs have been used for treating patients with CKD, few study demonstrated that TCMs were applied to treatment kidney diseases through targeting TGF-β/Smad signaling pathway.…”
Section: Natural Products As An Alternative Therapy Against Tubuloint...mentioning
confidence: 99%